Igrišča v digitalnem mestu - Nekou, Yasaman (Urbani izziv, 2022)
Today, the use of technological devices is commonplace among children, which has also diminished children’s presence in the city. Although children, as novel citizens, develop some of their skills (such as social, mental, and educational skills) in the city, many children face some kind of city exclusion. Therefore, the way the physical environment of their city is shaped and how children interact with it plays a principal role in child engagement. A child-friendly city can be a place to engage children using contemporary tools such as augmented reality (AR), which helps children communicate better and fosters abilities such as spatial cognition and physical and social skills in the physical and digital world. This study explores various examples and analyses the child-friendly city features of each. This article presents AR and its capabilities as a potential tool utilized in the city to pave the way toward a child-friendly mediated city – an inclusive social urban environment where children play or spend their leisure time and effectively mature into adulthood.
Keywords: augmented reality; child-friendly cities; digital cities; digital social engagement; digitalna mesta; otrokom prijazna mesta; razširjena resničnost; socialna vključenost v digitalnem okolju; urban perception; zaznavanje mestnega prostora